Gastro-intestinal in vitro digestions of protein emulsions monitored by pH-stat: Influence of structural properties and interplay between proteolysis and lipolysis. (1st May 2020) - Mat, D.J.L.; Souchon, I.; Michon, C.; Le Feunteun, S.
Graphical abstract: Highlights: Four protein emulsions with varied nano and microstructures were prepared. They were submitted to in vitro gastro-intestinal digestions (Infogest protocol) Gastro-intestinal hydrolyses of both lipids and proteins were assessed by pH-stat. Orlistat can be used to distinguish pancreatic hydrolysis of proteins and lipids. Main influencing factors were the bulk phase physical state and oil droplet sizes. Abstract: This study describes an experimental design, based on pH-stat, to rapidly screen and assess food formulation effects on the degrees of hydrolysis (DH) of both proteins and lipids throughout in vitro gastro-intestinal digestions. This approach was used to quantitatively compare and hierarchize key structure parameters of protein emulsions. Six matrices (15 wt% whey proteins, 0 or 10 wt% oil), each differing by at least one structure characteristic, were studied. The physical state of the bulk and the oil droplet size were the major structural levers to modulate the hydrolysis of proteins (final DH between 51.7 and 58.3%) and lipids (final DH between 46.9 and 72.7%), with non-trivial interplays between proteolysis and lipolysis. Additionally, pH-stat measurements in presence of a pancreatic lipase inhibitor proved to be an efficient way to widen the scope of the proposed experimental approach to foods that are intrinsically made of both proteins and lipids.